2012
DOI: 10.1155/2012/382810
|View full text |Cite
|
Sign up to set email alerts
|

A Security-Performance-Balanced User Authentication Scheme for Wireless Sensor Networks

Abstract: The uses of wireless sensor networks have increased to be applicable in many different areas, such as military applications, ecology, and health applications. These applications often include the management of confidential information, making the issue of security one of the most important aspects to consider. In this aspect, a user authentication mechanism that allows only legitimate users to access the network data becomes critical for maintaining the confidentiality and integrity of the network information.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 19 publications
0
79
0
Order By: Relevance
“…This section compares the security features and performance of our scheme with those of other related recently proposed schemes of Althobaiti et al [29], Yoo et al [52], Sun et al [53], Xue et al [54], and Jiang et al [55]. [29] Five messages (864 bits) [52] Six messages (1824 bits) [53] Five messages (1296 bits) [54] Four messages (2256 bits) [55] Four messages (1920 bits) Ours…”
Section: Performance and Functionality Comparisonmentioning
confidence: 97%
See 1 more Smart Citation
“…This section compares the security features and performance of our scheme with those of other related recently proposed schemes of Althobaiti et al [29], Yoo et al [52], Sun et al [53], Xue et al [54], and Jiang et al [55]. [29] Five messages (864 bits) [52] Six messages (1824 bits) [53] Five messages (1296 bits) [54] Four messages (2256 bits) [55] Four messages (1920 bits) Ours…”
Section: Performance and Functionality Comparisonmentioning
confidence: 97%
“…As a result, the total communication cost of our scheme becomes 832 bits. On the other hand, the communication overheads of Althobaiti et al scheme [29], Yoo et al scheme [52], Sun et al scheme [53], Xue et al scheme [54], and Jiang et al scheme [55] are 864, 1824, 1296, 2256 and 1920 bits, respectively. It is thus clear that our scheme is efficient.…”
Section: Performance and Functionality Comparisonmentioning
confidence: 99%
“…However, Yoo et al [15] found this improvement remains vulnerable. The reason is that secret parameters used by different users are uniform.…”
Section: Parallel Attack/no Protection Against Forgerymentioning
confidence: 99%
“…In 2010, Yuan et al [13] provided a bio-metric based scheme but it is unprotected from node capture and denial of service attack. In 2012, Yoo et al [14] designed a scheme that provides secure session key and mutual authentication. In 2013, Xue et al [15] designed a mutual authentication scheme based on temporal information.…”
Section: Related Workmentioning
confidence: 99%